Authenticity and relocation of built heritage: the urban transformation of Kiruna, Sweden. Issue 2 (15th May 2017) - Sjöholm, Jennie
Abstract : Purpose: The purpose of this paper is to investigate how different notions about the conservation of built heritage develop in a situation of structural change that demands either the demolition or relocation of a large number of historic buildings. Design/methodology/approach: The analysis is based on a case study of the on-going urban transformation of the Swedish mining town Kiruna. The investigation was based on the text analysis of urban planning documents and media reporting, which was used to distinguish stakeholders' positions towards conservation based on authenticity aspects. Findings: The conservation goals of the urban planning process are unclear and the stakeholders have conceptually different views regarding which parts of the town's built heritage are of significance, which negatively affects the ability to make well informed, transparent and intelligible management decisions. Stakeholder views on the management of built heritage span from the relocation of a few, single historic buildings to maintaining the integrity of the town as a heritage site by moving a significant number of buildings. Research limitations/implications: The Kiruna case, being exceptional because conservation in situ is impossible, has the potential to highlight the relation between single historic buildings and the integrity of an urban heritage site, as well as implications for conservation on the urban scale. Originality/value: This investigation contributes to knowledge of built heritage in situations of structural change, which is of concern for planning and conservation practice. Currently, many urban areas are under pressure of transformations or destruction.